2006
DOI: 10.1378/chest.129.4.954
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Mortality Outcome Associated With Prolonged Admission to the ICU

Abstract: ICU Long-term Mortality Outcome Associated With Prolonged Admission to the This information is current as of April 19, 2006http://www.chestjournal.org/cgi/content/full/129/4/954 located on the World Wide Web at:The online version of this article, along with updated information and services, is may be reproduced or distributed without the prior written permission of the copyright holder. Long-term Mortality Outcome Associated With Prolonged Admission to the ICU* Kevin B. Laupland, MD, MSc; Andrew W. Kirkpatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
4
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 21 publications
7
81
4
8
Order By: Relevance
“…However, the risk to succumb in ICU was higher in long-term patients and seems to be consistent with previously published data [28]. The mortality rate in the present long-term patient cohort after discharge from ICU appears to be similar than previously reported with a trend to improved outcome after surviving the acute illness [29]. The present study confirmed that long-term ICU survivors have no unfavourable outcome compared to "short-term" ICU survivors [17,27].…”
Section: Discussionsupporting
confidence: 92%
“…However, the risk to succumb in ICU was higher in long-term patients and seems to be consistent with previously published data [28]. The mortality rate in the present long-term patient cohort after discharge from ICU appears to be similar than previously reported with a trend to improved outcome after surviving the acute illness [29]. The present study confirmed that long-term ICU survivors have no unfavourable outcome compared to "short-term" ICU survivors [17,27].…”
Section: Discussionsupporting
confidence: 92%
“…First of all, a classification is made based on whether a patient will have a prolonged stay or not. To recapitulate, a prolonged stay is defined, following Laupland et al [29], as Φ > 10. A Φ histogram can be seen in Figure 6.…”
Section: Prolonged Stay Predictionmentioning
confidence: 99%
“…5,28,29 The majority of deaths in the surgical ICU occur after a prolonged hospital course complicated by multiorgan failure with intermittent periods of improvement and deterioration. [30][31][32] These cases may provide unique challenges to providing patients and families with prognostic information. In addition, the primary ethical principle governing care in the surgical ICU may be different than that in a nonsurgical ICU, with more focus on a covenantal ethic rather than an ethic of scarce resources.…”
Section: Documentation Of Palliative Carementioning
confidence: 99%